FAKTOR PENUNJANG PEMBINAAN DISIPLIN KERJA PEGAWAI KANTOR DESA RAMBAH KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - -, Hamdan (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
Along With reform bearing area autonomy, effort to apply principle of good governance have disseminated area keseluruh of is including sub-province of Rokan pate; Upstream to apply the the principle solely for penyelenggara of service of Countryside office of terbaik di Rokan Pate; Upstream for the agenda of improving society teraan kesejah. One of The real occurrence that happened {in} Office Countryside of Rambah District of downstream Rambah, is the lack of service of officer of Countryside office of rambah District of Rambah Downstream. Pursuant to above phenomenon {of} writer interest to {do/conduct} research entitling factor Sopporter of construction of Discipline work At Officer of Officer Countryside of Rambah, Rokan Pate; Upstream. This research is {done/conducted} to know factor supporter of construction of discipline work Officer Of Office Countryside of Rambah, Rambah Downstrem. This Research use descriptive research type, population in this research {of} officer of countrysideOffice of Rambah District of Rambah go downstream counted 7 people, of him 7 people by using saturated sampling tekhnik. Pursuant to research result got that factor supporter of construction of discipline officer of Office Countryside of RambahDistrict of Rambah go downstreamis motivation with value 26 (38,2%), practice and education 6 (85,7%).Leadership 11 (78,5%), straightening of discipline pass law 31 (49,2%). Pursuant to research result that motivation factor , practice and aducation , discipline work Officer Of Office Countryside of Rasmbah , Rambah Downnstream, while factor prosperity Do not.